Central line-associated bloodstream infections in neonates - Hye Jung Cho; Hye-Kyung Cho (Korean Pediatric Society, 2019)
Newborn infants, including premature infants, are high-risk patients susceptible to various microorganisms. Catheter-related bloodstream infections are the most common type of nosocomial infections in this population. Regular education and training of medical staffs are most important as a preventive strategy for central line-associated bloodstream infections (CLABSIs). Bundle approaches and the use of checklists during the insertion and maintenance of central catheters are effective measures to reduce the incidence of CLABSIs. Chlorhexidine, commonly used as a skin disinfectant before catheter insertion and dressing replacement, is not approved for infants <2 months of age, but is usually used in many neonatal intensive care units due to the lack of alternatives. Chlorhexidine-impregnated dressing and bathing, recommended for adults, cannot be applied to newborns. Appropriate replacement intervals for dressing and administration sets are similar to those recommended for adults. Umbilical catheters should not be used longer than 5 days for the umbilical arterial catheter and 14 days for the umbilical venous catheter. It is most important to regularly educate, train and give feedback to the medical staffs about the various preventive measures required at each stage from before insertion to removal of the catheter. Continuous efforts are needed to develop effective and safe infection control strategies for neonates and young infants.